A CLINICAL PHARMACOLOGICAL APPROACH TO THE RATIONAL USE OF DRUGS IN DEPRESSIVE SYNDROME - Urinboyev Lochinbek Khasanboy ugli (Galaxy International Interdisciplinary Research Journal, 2024)
A review of the literature on the neurobiological mechanisms of depressive disorders, which presents the role of biochemical changes in the cholinergic, serotonergic, dopaminergic and other neurohumoral systems in the development of depression. Modern approaches to the pharmacocorrection of depressive disorders are discussed in detail, and the question of the prospects of treating depression with anticholinergic drugs is also raised.